One-Child Policy, Marriage Distortion, and Welfare Loss - Wei Huang; Yinghao Pan; Yi Zhou (Review of Economics and Statistics, 2025)
We investigate how exposure to the One-Child Policy (OCP) during early adulthood affects marriage and fertility in China. Exploring fertility penalties across provinces over time and the different implementations by ethnicity, we show that the OCP significantly increases the unmarried rate among the Han ethnicity but not among the minorities. The OCP increases Han-minority marriages in regions where Han-minority couples are allowed for an additional child, but the impact is smaller in other regions. Finally, the deadweight loss caused by lower fertility accounts for 10 percent of annual household incomes, and policy-induced fewer marriages contribute to 30 percent of the fertility decline.